Computed tomography evidence of fluid in the hernia sac predicts surgical site infection following mesh repair of acutely incarcerated ventral and groin hernias. Issue 1 (July 2017) - Loftus, Tyler J.; Go, Kristina L.; Jordan, Janeen R.; Croft, Chasen A.; Smith, R. Stephen; Moore, Frederick A.; Efron, Philip A.; Mohr, Alicia M.; Brakenridge, Scott C.
Abstract : BACKGROUND: Mesh placement during repair of acutely incarcerated ventral and groin hernias is associated with high rates of surgical site infection (SSI). The utility of preoperative computed tomography (CT) in this setting is unclear. We hypothesized that CT evidence of bowel wall compromise would predict SSI while accounting for physiologic parameters. METHODS: We performed a 4-year retrospective cohort analysis of 50 consecutive patients who underwent mesh repair of acutely incarcerated ventral or groin hernias. We analyzed chronic disease burden, acute illness severity, CT findings, operative management, and herniorrhaphy-specific outcomes within 180 days. The primary outcome was SSI by the Centers for Disease Control and Prevention criteria. Multiple logistic regression was performed to identify independent predictors of SSI. RESULTS: Eighty-four percent of all patients were American Society of Anesthesiologists class III or IV, 28% were active smokers, and mean body mass index (BMI) was 35 kg/m 2 . Fifty-four percent had ventral hernias, 40% had inguinal hernias, and 6% had femoral or combined inguinal/ femoral hernias. Seventy percent of preoperative CT scans had features suggesting bowel compromise, abdominal free fluid, or fluid in the hernia sac. Surgical site infection occurred in 32% of all patients (8% superficial, 24% deep or organ/space). The strongest predictors of SSI were CT evidence of fluid in the hernia sac (odds ratio [OR], 8.3; 95% confidence interval [CI], 1.7–41), initial heart rate 90 beats/min or greater (OR, 6.3; 95% CI, 1.1–34), and BMI 35 kg/m 2 or greater (OR, 5.8; 95% CI, 1.2–28). Surgical site infection rates were significantly higher among patients who had CT evidence of fluid in the hernia sac (56% vs. 19%, p = 0.012). CONCLUSIONS: More than half of all patients with CT scan evidence of fluid in the hernia sac developed an SSI. Computed tomography evidence of fluid in the hernia sac was the strongest predictor of SSI, followed by heart rate and BMI. Together, these parameters identify high-risk patients for whom better strategies are needed to avoid SSI without sacrificing durability. LEVEL OF EVIDENCE: Prognostic study, level III; Therapeutic, level IV.